Relating Compulsivity and Impulsivity With Severity of Behavioral Addictions: A Dynamic Interpretation of Large-Scale Cross-Sectional Findings - Demetrovics, Zsolt; van den Brink, Wim; Paksi, Borbála; Horváth, Zsolt; Maraz, Aniko (Frontiers in Psychiatry, 2022)
Background and aim: Impulsivity and compulsivity are two key temperament traits involved in behavior regulation. The aim of this study was to test several existing theories in explaining the role of impulsivity and compulsivity in symptom severity in various behavioral addictions. Methods: Data were collected from a (representative) general population sample (N=2,710, mean age:39.8 years (SD:13.6), 51% woman), and from people who are at increased risk of having a behavioral addiction (N=9,528 in total, mean age: 28.11 (SD:8.3), 34.3% woman), including people with problematic gaming and internet use, pathological gambling, exercise dependence, compulsive buying and work addiction. Symptom severity, reward driven impulsivity and relief driven compulsivity were assessed. Results: For non-problematic groups, impulsivity is present to about the same extent as compulsivity, whereas for problematic groups, compulsivity dominates over impulsivity in all groups (except for gambling). The strength of the correlation between impulsivity and compulsivity is higher in more severe forms of the disorders (from r=0.18 to r=0.59 in the representative population). Discussion: Based on these data, it appears that relief-driven behavior (negative reinforcement) dominates over reward-driven behavior (positive reinforcement) in more severe cases of a behavioral addiction. Conclusion: This is the first large-scale study to find empirical support for the neuroscientific theory on the dominance of compulsivity (“needing”) over impulsivity (“wanting”) in more severe cases of a behavioral addiction. Although longitudinal research is needed, a possible shift from impulsivity to compulsivity takes place, similar to substance use addictions, which maintains the circle of addiction.